1990
DOI: 10.1111/j.1432-1033.1990.tb15523.x
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cation biding to reduced and octanoyl acyl‐carrier protein

Abstract: Mn(I1) EPR binding studies with reduced acyl-carrier protein (ACP-SH) strongly suggest the presence of two relatively high-affinity manganese-binding sites (average &/site z 80 pM) at physiological pH. Lowering the pH or titrating with sodium chloride reduces the average number of bound divalent cations and decreases the binding affinity. This is consistent with the idea that anionic ligand(s), e. g. the carboxylate of glutamic or aspartic acid, on the protein are involved in manganese ion coordination. At pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
(21 reference statements)
5
18
0
Order By: Relevance
“…2B). This stacked conformation is also observed in the EcACP structure (6) and positions the residues optimally for cation-pi interactions (33) and is consistent with the observation that His-75 in EcACP has an elevated pK a between 7.5 and 8.0 (34). Fig.…”
Section: Resultssupporting
confidence: 88%
“…2B). This stacked conformation is also observed in the EcACP structure (6) and positions the residues optimally for cation-pi interactions (33) and is consistent with the observation that His-75 in EcACP has an elevated pK a between 7.5 and 8.0 (34). Fig.…”
Section: Resultssupporting
confidence: 88%
“…6A) and K + ions (not shown) do not inhibit LpxD activity. These findings are consistent with reports that ACP has a high affinity for both Ca 2+ and Mg 2+ , but only a weak affinity for Na + and K + (37,38). Fig.…”
Section: Role Of Acyl Carrier Protein In Bindingsupporting
confidence: 93%
“…These findings are supported by previous reports, which showed that the E. coli ACP, and more recently Vibrio harvey ACP bind Ca 2+ with high affinity [54][55][56]. However, the role of Ca 2+ and ACP has not been analyzed in vivo.…”
Section: Casupporting
confidence: 87%